2015
DOI: 10.1007/s00402-015-2296-5
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary nailing of humeral shaft fractures: failure analysis of a single centre series

Abstract: IMN is a valid therapeutic option for humeral shaft fractures. Good surgical technique and soft tissue handling are important for good outcome. Currently, patient demands are receiving greater consideration. In an era where early full range of motion and rapid return to work with minimal scarring is mandatory for most patients, the use of IMN will most likely increase in popularity in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Similar case studies have been reported. Metsemarkers reported 5 patients (4%) who had early technical failures that required revision surgery [5]. In one case, the patient incurred an iatrogenic fracture during retrograde nailing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar case studies have been reported. Metsemarkers reported 5 patients (4%) who had early technical failures that required revision surgery [5]. In one case, the patient incurred an iatrogenic fracture during retrograde nailing.…”
Section: Discussionmentioning
confidence: 99%
“…The major disadvantages of external fixators are the length of operation time required, pin-tract infections, and the large size of the frame, resulting in significant discomfort for the patient. Intramedullary nailing, which has been used by many surgeons in the treatment of humeral nonunions [4,5], is an accepted technique for the treatment of humeral diaphyseal nonunion, and is also an established method for the treatment of highenergy long bone fractures, especially in a polytrauma setting and in osteoporotic, impending and pathological fractures. The technical errors and complications after intramedullary nailing of humeral diaphyseal nonunion have been recorded and discussed in only a limited number of studies [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery is considered when this conservative treatment fails to maintain the stability of reduction, open fracture, or other combined injuries. Many surgical techniques have been introduced to correct humeral shaft fractures, and there have been debates regarding their clinical indications 2. One of the standard surgical treatments is closed reduction and internal fixation using antegrade intramedullary nails.…”
Section: Introductionmentioning
confidence: 99%
“…One of the standard surgical treatments is closed reduction and internal fixation using antegrade intramedullary nails. This technique has several potential advantages over other methods, including open reduction and internal fixation with plates, in terms of reduced disruption to the surrounding soft tissue and greater preservation of extramedullary vascularity around the fracture site 23. However, it can be difficult to perform a closed reduction or obtain the required stability from fixation with an intramedullary nail in highly unstable fractures of the humeral shaft in which there are complex or severely-displaced fragments, and such difficulties could result in delayed union or non-union of the bone fragments 4.…”
Section: Introductionmentioning
confidence: 99%